THE EFFECT OF COMPANY SIZE AND CORPORATE SOCIAL RESPONSIBILITY ON TAX AGGRESSIVENESS, WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE (An Empirical Study of Companies in the Non-Cyclical Consumer Goods Sector Listed in Indonesia from 2020 to 2022) - ERIN APRIANI (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
This study aims to examine and analyze the effects of Firm Size and Corporate Social Responsibility (CSR) on Tax Aggressiveness, with Good Corporate Governance (GCG) serving as a moderating variable. CSR disclosure was measured based on the Global Reporting Initiative (GRI) Standards 2021 using information obtained from the companies' sustainability reports. The study population consisted of 87 Non-Cyclical Consumer Goods companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Using a purposive sampling method, 20 companies were selected as the research sample. Data were analyzed using moderated regression analysis (MRA) and processed with SPSS version 25. The results indicate that Firm Size has a positive effect on Tax Aggressiveness, while Corporate Social Responsibility has a negative effect on Tax Aggressiveness. Furthermore, Good Corporate Governance is found to moderate the relationship between Firm Size and Tax Aggressiveness, as well as the relationship between Corporate Social Responsibility and Tax Aggressiveness.